Key factors leading to effective performance management at a medical scheme company in South Africa. - Petro, Heather Mary (My University, 2016)
Effective performance management (PM) results in high performing employees who are engaged, creative, passionate and who continuously learn and develop. Worldwide organisations implement traditional performance management systems (PMS) with the aim of achieving effective PM, yet the literature reveals that many organisations report that their PMS are ineffective and cumbersome. Numerous factors that influence PM have been identified in the literature, however, there is no consensus regarding what the key factors are that lead to effective PM. This research employs a case study research design at a high performing medical scheme company in South Africa. The medical scheme company operates in the mature, highly competitive private healthcare industry where superior service provision relies on high performing employees. In order to identify the key factors influencing PM effectiveness, 14 one-on-one interviews were conducted with managers and two focus groups were conducted with a total of 12 employees. The key factors were identified using Thematic Content Analysis and they are: High quality manager-employee relationships built on trust and respect; A supportive, high performance organisational culture; High frequency interaction between managers and employees; Active engagement of both the managers and employees in PM; Manager’s ability to identify and manage employee expectations and behavioural drivers; Leader and employee traits, knowledge, skills and abilities; The structure and function of the PMS; Effective communication across the organisation; A clear link between performance and rewards; Alignment between organisational strategy and employee goals and PM training for managers. The key factors are similar to the internal aspects in the McKinsey’s 7-S framework and there also appear to be multiple interconnections and synergies between the key factors (Waterman, Peters, & Phillips, 1980). Thus effective PM at the company requires an integrated, multidimensional approach that focuses not only on the key factors that were identified, but also on creating alignment and synergy between the key factors.
MBA Thesis
Keywords: Performance -- Management,Personnel management -- South Africa.